The sweet in-between [large type] : a novel - Reynolds, Sheri (Center Point Pub., 2009)
Desperate for a place to belong with her father in prison and her mother dead, teenager Kenny Lugo finds a less-than-idyllic home with her Aunt Glo, her father's struggling girlfriend, and her children, until she finds redemption from an unexpected source following the killing of a college girl in the house next door.